Heritage Education as a Support of Cultural Identity: A Literature Review - a Venturo Huares, Rocio Vern (2024)
Although cultural heritage has great potential, it is often ignored that it has the power to weave our identity. Its definition is related to the value provided by people who identify with them. For this reason, the objective was to review the theoretical conceptions and educational practice of the use of heritage to revalue its use as an educational resource and as an identity element, recognizing the importance of heritage education, whose strategies and methods use heritage as a resource. didactic. In this study, the method used is descriptive documentary research and narrative review is used; This includes research that demonstrates the topic since the creation of the term, its evolution, use, contributions and a look at a near future in which it is included in educational institutions. Among the main results, it is considered that the teaching of heritage should be included in the curricular programs of educational institutions, since, although there are courses related to history, they are not enough, because they do not cover all the heritage wealth. This is a transversal resource that can be included in the various curricular areas, as demonstrated by the literature reviewed. Its relevance lies in the fact that heritage education promotes the acquisition of emotional, reflective and critical skills, favoring the comprehensive development of students.